PENGARUH MOTIVASI DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN SMK KSATRYA JAKARTA (Universitas Teknologi Muhammadiyah Jakarta (UTM Jakarta), 2019)
This study aims to examine and analyze the effect of Work Motivation and Discipline partially and or jointly on Employee Performance in Ksatrya Vocational High School. The research data was taken from a survey conducted on all employees at the Kstrya Vocational School. From a population of 46 employees using the Solvin formula a sample of 41 respondents was taken. The research method used is linear regression with 2 independent variables processed using SPSS. The results of the study stated that the coefficient of determination 0.550, which means the percentage contribution of the influence of independent variables (motivation and work discipline) to the dependent variable (employee performance) of 55.0% The remaining 45.0% is influenced or explained by other variables not included in this research model . The results showed that partially, Work Motivation and Discipline variables significantly positive effect on Employee Performance. And together (simultaneously), there is a significant influence of Work Motivation and Discipline on Employee Performance at SMK Ksatrya Jakarta.